1 ANALISIS PENDAPATAN USAHATANI DAN PEMASARAN TANAMAN HIAS MAWAR MERAH DI DESA SIDOMULYO KOTA BATU - hermanto hermanto; Sri Hindarti; Dwi Susilowati (Program Studi Agribisnis, 2019)
ABSTRACTThe research objective was to analyze the income of red rose ornamental plants farming, and to describe the marketing channels and marketing efficiency of red rose ornamental plants. The analytical method used is descriptive and quantitative analysis method, which consists of four approaches (a) RC / ratio analysis (b) Marketing margins (c) Market integration (d) Price transmission elasticity. The results of the descriptive analysis explained that the RC / ratio was 5.19. and there are two marketing channels, namely I: Farmers, big traders, out-of-town traders. Channel II: Farmers, Middlemen, Retailers, Consumers. The functions of marketing carried out by farmers: Middlemen, purchasing, transportation, grading, loading and unloading. Wholesalers: purchasing, transportation, grading, loading and unloading. Retailers: purchasing, transportation, loading and unloading. Out-of-town traders: Purchasing, transportation, loading and unloading. The results of quantitative data analysis can be concluded if the RC / ratio value is more than 1 then farming is profitable and feasible to cultivate. While the market structure indicates a monopoly market, this can be seen from the price transmission elasticity (ը) of 0.13.Keywords: Red rose farming, marketing channels, marketing efficiency